II Consensus of the Brazilian Society of Dermatology for the treatment of alopecia areata - Paulo Müller Ramos; Alessandra Anzai; Bruna Duque-Estrada; Daniel Fernandes Melo; Flavia Sternberg; Leopoldo Duailibe Nogueira Santos; Lorena Dourado Alves; Fabiane Mulinari-Brenner (Anais Brasileiros de Dermatologia)
Abstract Background: Alopecia areata is a highly frequent disease with great variability in clinical presentation, severity, and prognosis. It has a significant negative impact on quality of life, especially in the moderate and severe forms. Objective: To disseminate guidelines, prepared by a group of Brazilian experts, for the treatment and follow-up of patients with alopecia areata. Methods: Eight specialists from different university centers with experience in alopecia areata were appointed by the Brazilian Society of Dermatology to reach a consensus on its treatment. Using the adapted DELPHI methodology, relevant elements were considered and then an analysis of the recent literature was carried out and the text produced. Consensus on the guidelines was defined with the approval of at least 70% of the panel of experts. Results/Conclusions: Treatments vary according to patient age and disease severity. Intralesional injectable corticosteroid therapy was considered the first option for localized disease in adults. In severe cases, Janus Kinase inhibitors are the treatment with the highest levelof evidence. Systemic corticosteroid therapy and immunosuppressants (corticosteroid-sparing agents) are also options in these cases. Contact immunotherapy (diphencyprone) is an alternative for stable extensive cases. The assessment of side effects is as important as the hair regrowth rate.